OS 15-06 SEQUENTIAL ACTIVATION OF INTRARENAL ACE/ACE2 AS THE PROGRESSION OF HYPERTENSIVE NEPHROPATHY IN 2-KIDNEY 10CLIP (2K1C) GOLDBLATT RATS. (September 2016) - Kim, Yang Gyun; Lee, Sangho; Moon, Ju Young; Kim, Se Yeon; Lee, Yu Ho; Song, Seok Jong; Jeoung, Kyung Whan; Lee, Tae Won; Ihm, Chun Gyu
Abstract : Objective: Intrarenal renin-angiotensin system (RAS) had an important role to generate and maintain hypertension in 2-kidny 1-clip (2K1C) rats. This study purposed to assess how various intrarenal RAS components of 2K1C rats contributed to hypertension in different parts (cortex, medulla) of both sides (CK; clipped-kidney, NCK; non-clipped kidney) at different times (2 weeks; 2w and 5 weeks; 5w after clipping operation). Design and Method: We conducted to insert clip to left renal artery or sham operation to SD rats, then systolic blood pressure (SBP) was measured at one week interval. Kidney tissues were prepared for molecular and pathologic analysis in 2w and 5w after operation. Results: SBP increased in 2K1C rats within 1 week followed by clipping operation. At 2 w, juxtaglomerular apparatus (JGA) renin increased and ACE2 decreased in CK cortex, leading to elevate ACE/ACE2 ratio. At 5w, up-regulated ACE and down-regulated ACE2 with enhanced renin in collecting duct were found in both kidneys medulla, especially in NCK. Also AT1 R in CK cortex was not suppressed albeit reduced MasR, therefore, AT1 R/MasR ratio was elevated. Conclusions: Intrarenal RAS was changed depending on the time, part and sides of 2K1C rat kidneys. The attenuated ACE2 with augmented JGA renin in CK contributed to initiate hypertension and aggravated imbalanced ACE relative to ACE2 with activated renin in collecting duct have a key role to maintain hypertension.